International Climate Justice, Conflict and Gender – Scoping study - Duncanson, Claire; Bastick, Megan; Funnemark, Anne (University of Edinburgh, 2022)
Climate change, conflict and gender are mutually reinforcing dynamics that interact to destroy lives and livelihoods, especially for the most disadvantaged. From an analysis of Scottish Government work to date, and best practices in international policy and programming, this report suggests strategic policy opportunities through which the Scottish Government could boost its global roles in climate justice and gender equality, and contribute to peace and security.
Keywords: climate change; climate justice; gender; conflict